Observational Cross-Sectional Study on Dietary Supplementation among Adults in Eastern Croatia - Betilija Fadi Sekošan; Kenjeri, Daniela (Journal of Pharmacy and Nutrition Sciences, 2017)
The aim of the study was to gain insight into supplementation habits among adults in eastern Croatia. In cross-sectional study 466 adult participants were asked by anonymous survey about the type of supplement they take, the doses of the used supplement and the reasons and motivation for supplementation. Results revealed that participants most often chose essential nutrients (59 %) among which magnesium, multivitamins, B-complex vitamins, calcium and omega-3 fatty acids dominate. Supplementation is mostly aimed for disease treatment (46 %) and prevention (35 %) with musculoskeletal system and connective tissue diseases being the main cause followed by digestive system diseases. Most of the supplements were selected based on the recommendation of a health professional (76 %) and in line with recommendation by pharmacist or as stated at the product label (86 %).